Regional use of extracellular microvesicles of mesenchymal stromal cells in acute necrotizing pancreatitis in an experiment - O. A. Kudelich; G. G. Kondratenko; M. P. Potapnev; O. V. Klimenkova; N. V. Goncharova (Трансплантология (Москва))
Background. The significance of the problem of treatment of acute pancreatitis is due to an increase in the incidence with an increase in the number of necrotizing forms, accompanied by a high incidence of severe complications and high mortality.Objective. To identify the impact of regionally used extracellular microvesicles of mesenchymal stromal cells on the endogenous intoxication markers in acute necrotizing pancreatitis in the experiment.Material and methods. Acute pancreatitis was induced by the introduction of a 0.3 ml of 5% solution of non-ionic polyethylene glycol octylphenol ether detergent into the caudal part of the rat pancreas. The study was conducted on 42 adult Wistar rats, which were randomly divided into 4 groups. Group I (n=6) included intact animals, Group II (control group) (n=12) included rats with pancreatitis without treatment, Group III (n=12) consisted of rats with pancreatitis treated with analgesia + infusions of 0.9% sodium chloride solution (saline), Group IV (n=12) included rats with pancreatitis treated with analgesia+ saline infusions + regional application of extracellular microvesicles of mesenchymal stromal cells. Cells were obtained from the bone marrow of healthy animals. Microvesicles were obtained by differential centrifugation under sterile conditions. Microvesicles were administered one day after the pancreatitis induction through the catheter installed into the pathologically altered part of the pancreas. The dose of microvesicles was calculated as equivalent to (derived from) 1 million mesenchymal stromal cells. The hematological parameters, markers of the systemic manifestation of the pathological process (alpha-amylase, aspartate aminotransferase, alanine aminotransferase), the endogenous intoxication markers (lipid peroxidation activity, nitric oxide level), the systemic inflammatory response markers (tumor necrosis factor-alpha, interleukin-6) were studied on the 3rd and 7th day from the start of disease modeling.Results. Regional use of extracellular microvesicles of mesenchymal stromal cells in the treatment of acute experimental necrotizing pancreatitis at an early stage helped to normalize the level of blood platelets, reduce enzymeemia, elements of endogenous intoxication (interleukin-6, tumor necrosis factor-alpha), and the nitric oxide level.Conclusion. The early application of extracellular microvesicles of mesenchymal stromal cells in the treatment of acute necrotizing pancreatitis in an experiment has a positive effect on parameters, which are key links of pathogenesis and leading markers of this disease severity.